A Systematic Literature Review: The Role of Supply Chain Management in Enhancing Corporate Operational Performance - Urisnawati Rusli; Masnia Masnia; Asri Usman; Mediaty Mediaty (Universitas KH. Abdul Chalim Mojokerto, 2025)
In a company, operational performance must be achieved to fulfill the company's strategy. The main objective of this systematic literature review is to explore and identify the role of Supply Chain Management (SCM) in enhancing the operational performance of companies by providing an overview of SCM across various organizations. The research methodology involves analyzing scientific articles based on the criteria of selecting articles published within the time frame of 2019-2024 from journals in quartiles (Q1, Q2, Q3, and Q4). Utilizing the Watase Uake Prisma tool, 24 selected articles were produced. The results affirm that SCM plays a vital role in improving the operational performance of companies. The novelty of this article lies in its comprehensive approach to analyzing the role of SCM across different types of companies. Additionally, the authors integrate existing literature findings to identify the most commonly applied SCM strategies or practices. Overall, this research highlights the importance of effective SCM strategies and practices in enhancing operational efficiency, as well as identifying the challenges faced by companies in implementing SCM.